2018
DOI: 10.1055/b-006-149730
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Spine Surgery

Abstract: Surgical treatment of the degenerative disc disease has evolved from traditional open spine surgery to minimally invasive spine surgery including endoscopic spine surgery. Constant improvement in the imaging modality especially with introduction of the magnetic resonance imaging, it is possible to identify culprit degenerated disc segment and again with the discography it is possible to diagnose the pain generator and pathological degenerated disc very precisely and its treatment with minimally invasive approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…ICT-Nav allows for improved radiographic visualization of bony and soft tissue anatomy adjacent to the trajectory of approach thanks to the application of CT while maintaining tiny incisions. These capabilities have allowed spine surgeons to apply computer-assisted MIS for a myriad of procedures, including but not limited to pedicle screw fixation, transforaminal lumbar interbody fusion (TLIF), lateral/oblique lumbar interbody fusion (LLIF/OLIF), and vertebroplasty/kyphoplasty [ 1 , 41 ]. Improved pedicle screw accuracy using ICT-Nav as compared to fluoroscopy has been replicated in MIS as well [ 42 ].…”
Section: Available Navigation Technologies and Their Application To E...mentioning
confidence: 99%
See 4 more Smart Citations
“…ICT-Nav allows for improved radiographic visualization of bony and soft tissue anatomy adjacent to the trajectory of approach thanks to the application of CT while maintaining tiny incisions. These capabilities have allowed spine surgeons to apply computer-assisted MIS for a myriad of procedures, including but not limited to pedicle screw fixation, transforaminal lumbar interbody fusion (TLIF), lateral/oblique lumbar interbody fusion (LLIF/OLIF), and vertebroplasty/kyphoplasty [ 1 , 41 ]. Improved pedicle screw accuracy using ICT-Nav as compared to fluoroscopy has been replicated in MIS as well [ 42 ].…”
Section: Available Navigation Technologies and Their Application To E...mentioning
confidence: 99%
“…The authors reported high-quality clinical outcomes without surgical complications [ 50 ]. Nonetheless, there is a lack of literature comparing the relative effectiveness of navigation within endoscopic spine surgery against nonnavigated procedures [ 1 ]. As a result, future research comparing navigated versus nonnavigated approaches in ESS across a range of indications is needed; primary outcomes must include clinical benefit and radiation exposure to the operating room staff and patients, as well as cost.…”
Section: Available Navigation Technologies and Their Application To E...mentioning
confidence: 99%
See 3 more Smart Citations